NUMERICAL AND EXPERIMENTAL ANALYSIS OF THE STRENGTH OF TANKS DEDICATED TO HOT UTILITY WATER - BAŁON, Paweł; REJMAN, Edward; KIEŁBASA, Bartłomiej; SZOSTAK, Janusz; SMUSZ, Robert (Applied Computer Science, 2018)
The focus of this paper are experimental and numerical strength tests of domestic hot water storage tanks. The tests involved the verification of the minimum wall thickness for the assumed operating parameters while meeting all safety standards. The authors presented numerical and experimental analyses for the verification of strength parameters of axial cylindrical tanks due to the lack of methodological guidelines for this type of equipment. In order to verify the conducted theoretical considerations and calculations, experimental tests of samples of front welds produced with austenitic steel as well as a pressure test for the whole tank were conducted using a research test stand.